2003
DOI: 10.22358/jafs/67703/2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linseed and rapeseed or linseed and rapeseed oil on performance, slaughter yield and fatty acid deposition in edible parts of the carcass in broiler chickens

Abstract: The objective of the study was to investigate the effect of linseed and rapeseed or respective oils on performance indices, nutrient digestibility, metabolizable energy of diets, digesta viscosity, and yield and chemical composition of edible and non-edible parts of the carcass of broiler chickens, with particular attention to n-3 PUFA. Two experiments were performed on 134 female broiler chickens, randomly allocated to 3 groups of 22 birds (Experiment 1) or 2 groups of 24 birds (Experiment 2) and 10 birds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 19 publications
(50 reference statements)
10
41
1
1
Order By: Relevance
“…This supports the findings of many studies that the fatty acid profile of chicken meat depends on the dietary polyunsaturation level (Nguyen et al, 2003;Cortinas et al, 2004;Bou et al, 2005;Koreleski and Świątkiewicz, 2006;Jankowski et al, 2012). Increased dietary levels of vitamin E or both antioxidants in the diets with rape seeds and fish oil was associated with a lower n-6 PUFA content in breast and thigh meat and lower content of n-3 PUFA in thigh meat in comparison with group RF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports the findings of many studies that the fatty acid profile of chicken meat depends on the dietary polyunsaturation level (Nguyen et al, 2003;Cortinas et al, 2004;Bou et al, 2005;Koreleski and Świątkiewicz, 2006;Jankowski et al, 2012). Increased dietary levels of vitamin E or both antioxidants in the diets with rape seeds and fish oil was associated with a lower n-6 PUFA content in breast and thigh meat and lower content of n-3 PUFA in thigh meat in comparison with group RF.…”
Section: Discussionsupporting
confidence: 89%
“…An efficient way of enriching poultry meat with n-3 PUFA is supplementation of diets with feed components rich in n-3 PUFA of plant or animal origin (Nguyen et al, 2003;Koreleski and ABSTRACT. A total of 160 Ross 308 female broilers from day 22 to 35 of age were used to investigate the effects of vitamin E and selenium (Se) supplementation on performance, fatty acid profile and oxidative stability of meat enriched with n-3 fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, extrusion promoted creation of insoluble complexes from protein and dietary fibre components. Nguyen et al (2003) reported that the jejunal digesta from chickens fed rapeseed or soyabean-based diets were of similar viscosity, which was confirmed in this study. The viscosity of jejunal digesta was significantly lower, however, in the RCE group in comparison with the RC group.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the residual oil has a lower n-6/n-3 PUFA ratio than most of the fats used in broiler diets. Nguyen et al (2003) showed that broilers fed diets with rapeseed oil deposited fat with a low n-6/n-3 PUFA ratio in edible parts of the carcass, which can be considered beneficial for consumer health.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, however, they increased the concentration of long-chain omega-3 PUFA in the experimental diets and decreased SFA and MUFA. The beneficial effect of adding linseed oil, Camelina sativa oil, or fish oil to feed for other species (e.g., poultry) on the profile of animal tissues has also been demonstrated by other authors (Nguyen et al, 2003b;Jankowski et al, 2012;Pietras and Orczewska-Dudek, 2013). In our study, as the concentrations of ALA or LC omega-3 PUFA in the diets increased, the ratio of PUFA/SFA in the MLD increased, whereas the 18:2 n-6/18:3 n-3 and PUFA omega-6/omega-3 ratios decreased.…”
Section: Discussionmentioning
confidence: 66%